Локальне укріплення підошви виробок, що підтримуються в зруйнованому масиві - Сахно, І.; Ісаєнков, О.; Родзін, С. (Розробка родовищ, 2017)
Purpose. Justification of feasibility of non-explosive destruction of hard rock during in-seam workings based on the obtained dependences related to changes of physical and mechanical properties of non-explosive destructive mixtures (NDM) in the process of hydration in borehole charges causing crack growth in the near-hole area.
Findings. It has been experimentally proved that the footing rocks have a block discrete structure at a distance of at least half the width of inelastic deformations zone. The empirical dependences are obtained, describing footing bulging and horizontal compaction of rocks under the influence of loading, as a result of the disturbance of the rocks equilibrium state by mining operations for consolidated and non-consolidated rocks. Цель. Обоснование целесообразности локального укрепления пород почвы выработок, поддерживаемых в зоне разрушенных пород, исходя из зависимостей изменения горизонтального уплотнения пород почвы и их поднятия в полость выработок для различных схем локального укрепления.
Результаты. Экспериментально доказано, что породы почвы выработки на расстоянии не менее половины ширины зоны неупругих деформаций имеют блочно-дискретную структуру. Получены эмпирические зависимости поднятия подошвы и горизонтального уплотнения пород под воздействием нагрузки в результате нарушения равновесного состояния пород горными работами для укрепленных и неукрепленных пород. Мета. Обґрунтування доцільності локального зміцнення порід підошви виробок, що підтримуються в зоні розрушених порід, виходячи із залежностей зміни горизонтального ущільнення порід підошви та їх підняття в порожнину виробок для різних схем локального зміцнення.
Результати. Експериментально доведено, що породи підошви виробки на відстані не менше половини ширини зони непружних деформацій мають блочно-дискретну будову. Отримано емпіричні залежності підняття підошви й горизонтального ущільнення порід під впливом навантаження в результаті порушення рівноважного стану порід гірськими роботами для укріплених і неукріплених порід.